Renal trauma. (July 2017) - Veeratterapillay, Rajan; Fuge, Oliver; Haslam, Philip; Harding, Chris; Thorpe, Andrew
The kidney is the most commonly injured genitourinary organ, and renal involvement has been reported in 1–5% of all trauma cases. Two mechanisms of renal injury are described, namely blunt (direct blow to the kidney, rapid acceleration/deceleration or a combination) and penetrating (from stab or gunshot wounds), with blunt injuries being most common in the UK. It is important to keep an index of suspicion for renal trauma as given by the mechanism of the injury or in poly-trauma. Accurate assessment and resuscitation are vital in the initial management. Imaging with computed tomography is critical to the accurate grading of the injury and helps guide subsequent treatment. The approach to management of renal injuries has changed over time. During the past two decades, advances in cross-sectional imaging coupled with minimally invasive intervention strategies (like angiography, embolisation and ureteric stenting) for managing traumatic renal injuries have allowed increased renal preservation by reducing the need for major surgical intervention. Nowadays, the vast majority of blunt injuries (up to 95%) are managed conservatively with accumulated experience suggesting this is safe. However, there is still a role for open surgical exploration in patients with haemodynamic instability or those who fail initial conservative/minimally invasive management.